Influence of Pre-partum Habituation Training to Milking Routine on Post-partum Milking Behaviour and Performance of Primiparous Sahiwal cows (Indian Journal of Animal Production and Management, 2024)
The aim of the study was to find out the effect of pre-partum habituation training on post-partum  stress levels, milking behavior and production performance of primiparous Sahiwal cattle heifers. For  this study, 10 advanced pregnant Sahiwal heifers were allotted to two groups of 5 heifers each. The  T1 group was exposed to the environment of milking parlour and given training for milking for a period  of 15 days before calving. There was significant (P
Keywords: Habituation; Sahiwal heifers; stress; milking behavior; performance